Characteristics and elements of sustainable development of the food service market - Rakhimova Dilorom Sulaymonovna, (THE INNOVATION ECONOMY, 2026)
This article presents the views of both foreign and local researchers regarding the implementation of sus tainable development in the context of the sustainable advancement of the foodservice market. The study examines the characteristics of sustainable development, its implementation stages, sustainable development goals, and key elements. Based on the analysis of sustainable development processes within foodservice enterprises, relevant con clusions have beendrawn.